Higher heart rate intensity can negatively impact tactical decision-making and technical accuracy in small-sided games: a study on the effects of field size and scoring method manipulation - Qiao, W.; Hua, K.; Zhang, J.; Song, D.; Li, J.; Chen, X.; Liang, D. (Journal of Sports Science & Medicine, 2025)
This study investigated how varying task constraints - pitch size and the presence of a goal - affect psychophysiological intensity, technical execution, and tactical decision-making in small-sided games (SSGs). The study also examined correlations between intensities and technical and tactical performance. Thirty-six regional-level male youth soccer players (aged 16.5 ± 0.5 years) participated in a four-week intervention using a non-controlled, repeated-measures design within a single cohort. Players completed 3v3 SSGs under six conditions combining three pitch sizes (75, 100, and 125 m2 per player) and two task goals (ball possession vs. small goals). Each session included standardized warm-ups and three 4-minute bouts per condition. Psychophysiological responses were measured via Rating of Perceived Exertion (RPE) and heart rate monitoring (HRmean, % time in Zone 5). Technical actions (passes, receptions, dribbles, shots) and tactical decision-making (Passing Decision-Making index) were assessed through video-based analysis. Significant interactions (p < 0.001) between field size and scoring method were found for HR measures and passing. Ball possession games showed higher HRmean and HR Zone 5 across all field sizes compared to small-goal games (p < 0.001). However, even in small-goal games, HRmean and HR Zone 5 significantly increased with larger field sizes (p < 0.001). Small-goal games resulted in more successful dribbles (p < 0.001), with fewer successful passes on the smallest field. A moderate negative correlation was observed between HRmean and successful shots (r = -0.346, p = 0.039), and between time in HR Zone 5 and the passing decision-making index (r = -0.363, p = 0.029). The study suggests that both field size and scoring method significantly influence players` physiological responses, technical performance, and decision-making. Ball possession games and larger fields increase physical intensity and passing success, while smaller fields and small-goal games promote dribbling. However, higher physiological strain appears to negatively impact shooting effectiveness and decision-making quality, although these correlations are moderate and no definitive conclusions can be drawn or generalized.